The Link Analysis of the Pigmentary and Structural Characteristics of the High-Eutrophic Lake Phytoplankton - Sergey I. Sidelev (Журнал Сибирского федерального университета: Серия Биология, 2008)
The relation between pigmentary and structural characteristics of phytoplankton is analyzed by the example of a high-eutrophic lake (Lake Nero, Yaroslavl area) where grey-blue algae of planktotrichetic type prevail in phytoplankton. Strong positive correlation between chlorophyll “a” content in seston and phytoplankton biomass is noticed in concrete years. The regression lines with different tilt angles have been obtained at the comparative analysis of a chlorophyll - biomass relation with the previous researches (1987-1989) and it does not allow to determine a transitive factor between the total aglae biomass and chlorophyll amount in a separately taken reservoir even on the basis of a long-term supervision. Wide variability of the specific chlorophyll “a”content in a unit of raw phytoplankton biomass (0.05-3.97 %) is marked. The reasons of chlorophyll abundance fluctuations in phytoplankton are discussed. Of all the phytoplankton pigmentary parameters considered in this work (chlorophylls “b” and “c”, indexes Е480/Е664, Е430/Е664, Е450/Е480, carotenoids, pheopigments) the close and significant links of phytoplankton structural characteristics are found out only with pigmentary index Е450/Е480.This index is proposed to be used as a ratio parameter of certain phytoplankton taxonomic groups.